(untitled) (TEST BioLaw Journal - Rivista di BioDiritto, 2020)
Several neurotechnological devices that are in use today can both collect signals from the brain electro activity and send impulses to the brain. Thus, it is possible to intervene on brain activity in order to modify it and to transform it into usable and reproducible signals. This new kind of man-machine connection is going to have a deep impact on legal categories. This paper focuses on the notion of mental integrity and the consequent changes within its semantic field. What provides the guiding thread is the current debate on personal identity and autonomy of Deep Brain Stimulation patients. The conclusion outlines the possible philosophical background of the issues at stake.